PROFIL IBU BERSALIN DENGAN BAYI ASFIKSIA DI RSUD KOLONEL ABUNDJANI BANGKO TAHUN 2020 – 2021 - Siregar, Evi Andriani (Universitas Fort de Kock Bukittinggi, 2023)
Data from the World Health Organization IMR in the world in 2019 reached 28.2 per 1000 live births. The results of the Indonesia Demographic and Health Survey in 2017 showed AKN at 15 per 1000 live births and IMR at 24 per 1000 live births. Based on data at the Kolonel Abundjani Regional Hospital Bangko, it was found that the incidence of asphyxia neonatorum in 2019 was 119 cases, in 2020 there were 108 cases, and in 2021 there were 85 cases. The biggest cause of newborn mortality is asphyxia, which is 11.4%. This study aims to determine the profile of mothers in maternity with asphyxia babies at Kolonel Abundjani Regional Hospital Bangko in 2020-2021. This type of research is descriptive which consists of two variables, independent variables, namely age, education, parity, gestational age, PROM, prolonged labor, HB levels and leukocyte levels. The dependent variable is asphyxia infants. The sample in this study amounted to 193 using Total Sampling. The results of this study obtained profiles of mothers giving birth, namely maternal age 64.8% not at risk, education 30.1% high school, parity 80.8% not at risk, gestational age 62.2% not at risk, PROM 52.2% not at risk, parturition Duration 73.6% Not Long Parturition, HB Levels 52.3% Normal, and Leukocyte Levels 52.8% Abnormal. Based on the results of the research above, it is recommended that health workers and health service providers improve services, especially midwifery care for mothers in order to detect early risk factors for asphyxia so as to reduce the incidence of asphyxia in newborns.Keywords: Parity, PROM, Old Parturition, Hemoglobin, Leukocytes.References : 37 (2010-2021